#TITLE_ALTERNATIVE# - PUTRA ADI PERDANA (NIM 12205067); Pembimbing: Dr.-Ing Ir. Rudi Rubiandini R.S., TEGAR
Cementing operation is a process that can not be separated from the activities of oil and gas exploitation and the exploitation of geothermal energy. Cementing operations against an oil well, natural gas or geothermal wells, is expected to produce a condition in which the casing is cemented to the drill hole to function as expected. Cementation process itself can be divided into several stages, from the cement slurry making process, the pumping process, until the waiting on cement process (WOC). One of the parameters that need to be considered in the cementation process is cement thickening time, which is thickening time should not exceed the length of the pumping of cement, because if the cement harden before pumping time, it will hinder pumping process or can even stop the cementation process, on the one hand the thickening time also must be not too long, ideally after the pumping of cement, it is expected to cement had dried perfectly, because if too long will automatically add operational cost. But the reality on the ground, it is very hard to achieve this ideal condition. To overcome the above problems we can add additives to the cement, either in the form of accelerator to speed up the drying process and retarder to slow the drying process. In this paper conducted a laboratory study to determine the performance or the result of additives used in the temperature variation and also a certain concentration. This is to determine the actual performance of the additive is added, and also can be used to compare the performance of the additive with each other. Thus we expected to find out which additives are most effective and most efficient way to used.